Pelaksanaan Pembelajaran Jarak Jauh Melalui Internet Pada Guru SD Bina Karya Bekasi - Muratin (PARAMETER, 2022)
Learning outcomes are the abilities possessed by students after they receive the teaching and learning process carried out by educators. Assessment of learning outcomes has the aim of knowing the extent to which the learning process has been running. Learning outcomes can be seen through scores or grades after students take a test or test. Learning outcomes are categorized into three namely cognitive, affective, psychomotor. The learning outcomes of each student are different because they are influenced by many factors, including the school environment and family environment. The aims of this study were to: (1) explain the influence of the school environment on student learning outcomes in Islamic subjects at SD Bina Karya, (2) explain the influence of the family environment on student learning outcomes in Islamic subjects at SD Bina Karya, (3) explain the influence of the school environment and family environment on student learning outcomes in Islamic subjects at SD Bina Karya. Abstrak Hasil belajar adalah kemampuan-kemampuan yang dimiliki oleh siswa setelah ia menerima proses belajar mengajar yang dilakukan oleh pendidik. Penilaian hasil belajar memiliki tujuan untuk mengetahui sejauh mana proses pembelajaran yang telah berjalan. Hasil belajar dapat dilihat melalui skor atau nilai setelah siswa mengerjakan suatu tes atau ulangan. Hasil belajar dikategorikan menjadi tiga yaitu kognitif, afektif, psikomotoris. Hasil belajar setiap siswa berbeda karena dipengaruhi oleh banyak faktor yaitu diantaranya lingkungan sekolah dan lingkungan keluarga. Tujuan penelitian ini adalah untuk: (1) Menjelaskan pengaruh lingkungan sekolah terhadap hasil belajar siswa mata pelajaran Agama Islam di SD Bina Karya, (2) Menjelaskan pengaruh lingkungan keluarga terhadap hasil belajar siswa mata pelajaran Agama Islam di SD Bina Karya, (3) Menjelaskan pengaruh lingkugan sekolah dan lingkungan keluarga terhadap hasil belajar siswa mata pelajaran Agama Islam di SD Bina Karya.